(untitled) (Swiss Medical Weekly, 2025)
The health policy guiding principle of equitable access to healthcare faces barriers in the context of migration, on the part of both those affected and the health system. The operationalised measurement of health inequity, the training and sensitisation of healthcare professionals regarding needs-based care, diversity, transcultural and socio-medical aspects, and ensuring high-quality communication are among the measures that can contribute to reducing inequitable care (e.g. underuse) in this population.